Master of Arts in Education Management and Administration (MAEM) - Kabale University (Kabale University, 2022)
This programme is intended to train students to meet the social, psychological, and educational challenges of the 21st century. It focuses on the practical application of theory and current field practices to develop competence among students. It is designed in such a way as to help students wishing to pursue doctoral degrees to have a smooth transition from master’s to doctorate level. It gives students a constructive platform for reflecting, researching, and writing about contemporary issues in educational settings.